If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 3x = 61236 Combine like terms: 3x + 3x = 6x 6x = 61236 Solving 6x = 61236 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '6'. x = 10206 Simplifying x = 10206
| X-9/2=8 | | -44t^4+51t^3+5t^2=0 | | 3x+x+x-10=45 | | 799+25x=1000 | | 5(x+5)-5x(5-7x)= | | 26+-15+35= | | 9x+x=600 | | 6x^2-34x+48=0 | | 8x-3x=505 | | 1.25/0.5*10/10 | | 20x^3-36x^2+5x-9=0 | | 2w+4=l | | 10t-10=-2(-5t+6) | | 1/6x+13+9 | | -25x^2-25x-6=0 | | (w-2)=3 | | 2v-3=5 | | 2x+9/2-31=0 | | 3m-6m+7=0 | | w+2=3 | | 125+0.5x=145 | | x^(2/3)=4 | | -4x+8=2(2x-4) | | -27=-x+24 | | 12-(x+3)=74 | | 1/2x-7=11-1/2x | | C=3.50+1.25(16-1) | | -12x+24y-38-5x-4y-16= | | 3x+x-5=(x-2) | | x^(1/3)=5 | | 7.6=y-4.8 | | C=3.50+1.25(m-1) |